A Metataxonomic Approach Reveals Diversified Bacterial Communities in Antarctic Sponges - Ruocco, Nadia; Esposito, Roberta; Bertolino, Marco; Zazo, Gianluca; Sonnessa, Michele; Andreani, Federico; Coppola, Daniela; Giordano, Daniela; Nuzzo, Genoveffa; Lauritano, Chiara; Fontana, Angelo; Ianora, Adrianna; et al. (Marine Drugs, 2021)
Marine sponges commonly host a repertoire of bacterial-associated organisms, which significantly contribute to their health and survival by producing several anti-predatory molecules. Many of these compounds are produced by sponge-associated bacteria and represent an incredible source of novel bioactive metabolites with biotechnological relevance. Although most investigations are focused on tropical and temperate species, to date, few studies have described the composition of microbiota hosted by Antarctic sponges and the secondary metabolites that they produce. The investigation was conducted on four sponges collected from two different sites in the framework of the XXXIV Italian National Antarctic Research Program (PNRA) in November-December 2018. Collected species were characterized as Mycale (Oxymycale) acerata, Haliclona (Rhizoniera) dancoi, Hemigellius pilosus and Microxina sarai by morphological analysis of spicules and amplification of four molecular markers. Metataxonomic analysis of these four Antarctic sponges revealed a considerable abundance of Amplicon Sequence Variants (ASVs) belonging to the phyla Proteobacteria, Bacteroidetes, Actinobacteria and Verrucomicrobia. In particular, M. (Oxymycale) acerata, displayed several genera of great interest, such as Endozoicomonas, Rubritalea, Ulvibacter, Fulvivirga and Colwellia. On the other hand, the sponges H. pilosus and H. (Rhizoniera) dancoi hosted bacteria belonging to the genera Pseudhongella, Roseobacter and Bdellovibrio, whereas M. sarai was the sole species showing some strains affiliated to the genus Polaribacter. Considering that most of the bacteria identified in the present study are known to produce valuable secondary metabolites, the four Antarctic sponges could be proposed as potential tools for the discovery of novel pharmacologically active compounds.